2021
DOI: 10.1093/neuros/nyab223
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Neurosurgical Residency Applicants’ Letters of Recommendation

Abstract: BACKGROUND Letters of recommendation (LORs) are one of the most important components of the neurosurgical residency application. Studies in other fields and surgical subspecialties have found gender bias. OBJECTIVE To determine whether neurosurgical LORs contain significant linguistic gendered differences. METHODS We performed a retrospective review and lingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…8,12 Field et al found no linguistic differences in LORs based on gender for neurosurgical residents. 15 Other research has been conducted for urology, radiation oncology, orthopedic surgery, and ophthalmology residencies and transplant surgery fellowships. [9][10][11]13,14 There appears to be only one study of this nature for pharmacy residency programs by Rice et al, conducted at a single center for one application cycle, which found that women candidates' LORs contained more gendered, solitary/ reserved, and desire words than men candidates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12 Field et al found no linguistic differences in LORs based on gender for neurosurgical residents. 15 Other research has been conducted for urology, radiation oncology, orthopedic surgery, and ophthalmology residencies and transplant surgery fellowships. [9][10][11]13,14 There appears to be only one study of this nature for pharmacy residency programs by Rice et al, conducted at a single center for one application cycle, which found that women candidates' LORs contained more gendered, solitary/ reserved, and desire words than men candidates.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Gender bias in LORs has been studied in various medical residency and fellowship programs with mixed results. [8][9][10][11][12][13][14][15] In postgraduate pharmacy residencies, there is one single-center study that evaluated pharmacy residents' LOR for gender bias. 16 Besides lacking additional studies for gender bias in LORs, there are also no studies that tried to determine if gender bias might impact residency offers to interview, the next step in the process of obtaining a residency.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is critical to be aware of unconscious biases that can disadvantage highly qualified applicants, such as using "softer" rather than "standout" praise words, gender or ethnic stereotypic traits, or writing shorter letters for applicants who differ in gender, ethnicity, or orientation from the evaluator. [10][11][12] While neurosurgery is better at this than most specialties, 13 it is still important to recognize potential pitfalls. This is an important manuscript and we agree with their findings.…”
Section: Development Iterative Improvement and Future Directions Of T...mentioning
confidence: 99%
“…T he authors of the article "The Role of Gender in Neurosurgical Residency Applicants' Letters of Recommendation" performed a retrospective review of letters of recommendation (LOR) submitted for applicants who were offered an interview at their institution. 1 They report that within their cohort, there were more similarities among LOR for female and male applicants than there were differences. Their specific findings include that LOR for female applicants were more likely to have been written by female faculty, were longer, and were more likely to have the candidate described as "outstanding."…”
mentioning
confidence: 99%